Coronary Artery Calcium Score Improved Cardiovascular Disease Risk Prediction in Asymptomatic Patients - I Md Ady Wirawan; Rodney Wu; Malcolm Abernethy; Sarah Aldington; Peter Larsen (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2018)
This study examined whether coronary artery calcium score (CACS) has a betteraccuracy than the cardiovascular risk prediction chart (CRPC), and evaluate thereclassification improvement of CACS if it isused as a screening tool compared withthe CRPC. CACS has a better accuracy than the CRPC and reclassified a considerableproportion (39%) of a symptomatic patient into correct cardiovascular risk categories.CACS should be assessed in asymptomatic people with5-year CVD risk score of5-10% and 10-15%.